2001
DOI: 10.1097/00007632-200111150-00025
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Spontaneous Spinal Epidural Hematoma Without Surgery

Abstract: Spontaneous spinal epidural hematoma should be considered in the differential diagnosis of sudden onset of spinal cord compression in association with back pain. Patients initially presenting with severe neurologic dysfunction are potential candidates for conservative management if they demonstrate rapid and progressive improvement in neurologic function. Patients treated in this manner can have nearly complete restoration of function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(80 citation statements)
references
References 20 publications
1
77
0
2
Order By: Relevance
“…Stephen et al 16 reported two patients who spontaneously developed a rapid onset of neurological deficits and an equally rapid resolution of symptoms. Duffill et al 17 reported four patients with a rapid onset and early recovery of deficits caused by spontaneous epidural hematoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stephen et al 16 reported two patients who spontaneously developed a rapid onset of neurological deficits and an equally rapid resolution of symptoms. Duffill et al 17 reported four patients with a rapid onset and early recovery of deficits caused by spontaneous epidural hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…The neurological deficit could be caused by direct compression of the neural elements or due to ischemia caused by the pressure exerted by the hematoma on the blood vessels. Early resolution of symptoms has been attributed spontaneous decompression 16 of the hematoma in the epidural space, and patients who do not respond to decompression probably have suffered permanent vascular injury or permanent compressive myelopathy of the cord.…”
Section: Discussionmentioning
confidence: 99%
“…surgery can also be performed after more than 8 h. Contributing factors to the positive outcome may have been that complete ischemia did not occur as a result of moderate spinal cord compression. Hentschel and colleagues have reported on two cases with spontaneous resolution of spinal epidural hematomas without surgery (19). Another important fact is that the patient was given betamethasone during the observation period in the neurosurgical ward, which may have contributed to the outcome (20).…”
Section: Discussionmentioning
confidence: 99%
“…Conservative treatment is indicated for patients with mild neurological deficits, such as Frankel grade D-E 8 , or patients showing progressive neurological improvement 9,10 . Patients without neurological deficits can also be treated conservatively 4 .…”
Section: Casementioning
confidence: 99%